Localization of T-DNA Insertions in Petunia by Fluorescence in Situ Hybridization: Physical Evidence for Suppression of Recombination. - Ten Hoopen, R. (1996)
Using fluorescence in situ hybridization (FISH) with metaphase preparations, we localized a 4-kb single-copy T-DNA sequence in a group of petunia transformants. The selected T-DNAs previously had been shown to be linked to the phenotypic marker FI on chromosome II. Linkage analysis had revealed that recombination around the FI locus is suppressed in a wide cross relative to an inbred recombination assay. The localization of six FI-linked T-DNAs and the FI locus itself, using FISH, revealed a number of aspects of recombination in petunia: (1) the central region of chromosome II showed at least a 10-fold suppression of recombination in wide crosses relative to the distal region; (2) recombination in wide hybrids over two-thirds of the chromosome was extremely low; and (3) recombination between completely homologous chromosomes in an inbred cross also was suppressed in the central region. In addition, the T-DNAs were not evenly distributed along the chromosome, suggesting a possible preference for a distal position for T-DNA integration. Implications for such a preference are discussed.